(untitled) (Journal of the College of Basic Education, 2026)
The research aimed to identify the development of mathematical achievement and sustainable education dimensions among middle school students through the scientific stations strategy: An experimental study." The basic research sample consisted of first-grade middle school students, numbering (78) students, distributed into two groups: the first experimental and the second control. The research used the experimental method as a research approach, with a quasi-experimental design for two equivalent groups with a post-test. The research had two instruments: the first, an achievement test in mathematics consisting of (30) multiple-choice items with a test reliability coefficient of (0.76), and the second, a scale to measure sustainable education with its four dimensions, which consisted of (20) items distributed equally across its dimensions with a test reliability coefficient of (0.78). The research concluded in its results, according to the statistics of the data revealed by the statistical analysis, the superiority of the experimental group with a clear statistical significance over the control group, confirming the effectiveness of the scientific stations strategy in teaching mathematics on both direct academic achievement and sustainable education with its environmental, economic, social, and educational dimensions